English - Vucetic, Srdjan (Journal of Regional Security, 2022)
Will China’s rise lead to Chinese hegemony? Most International Relations scholars would answer in the negative, contending the road to a global hegemony remains well beyond Beijing’s interests and capabilities. In Asia, however, China’s formidable economy, technological advancement, rapidly modernizing military forces, and recent geopolitical moves look outright hegemonic – a fact that the United States attempts to “pivot” and “rebalance” to that region have put into sharp relief. To assess the prospects of a new regional hegemony, this article considers the “economic,” “security” and “cultural” relations of eleven Asian states with both Beijing and Washington. The overall results induce skepticism about the latter’s ability to reorder the region. Although growing and in some cases significant, China’s provision of international goods to neighboring countries still pales in comparison to that centered on the United States and its allies. Sightings of an Asian Pax Sinica are at best premature.